Minding mortality: A systematic review of the neural processing of death-related stimuli - Bengtson, Anna; Nordin, Ida; Parthemore, Joel; Revonsuo, Antti (Elsevier BV, 2026)
The human relationship with mortality has been widely studied in psychology, with extensive studies suggesting that death-related stimuli impact behavior even without reflective awareness. In recent decades, neuroimaging studies have yielded various contenders for brain regions underlying the online processing of death-related stimuli. To the best of our knowledge, we present here the first systematic review of these findings. We conducted a comprehensive search for studies where participants were presented with death-related and death-unrelated but negatively valenced (unpleasant) stimuli while undergoing functional brain imaging. We found seven functional magnetic resonance imaging studies with a total of 204 participants. Five of six within-group studies found that unpleasant stimuli consistently elicited increased insular activity, but only when it was unrelated to mortality. This novel finding—that insular deactivation alone marks the processing of death-related stimuli—suggests a critical difference between the neural processing of death-related and non-death related, unpleasant stimuli. We argue that preexisting explanatory frameworks fail to unite our results with findings on threat processing mechanisms in the insula or lack evolutionary plausibility. We present an alternative explanation: death might be unique in that it evades the insula's typical threat-assessment mechanisms.
Further research is needed to determine whether this neural signature is robust and what its function and consequences may be. A better understanding of how individuals process death-related information promises deeper insight into the human relationship with mortality, with significant implications for individuals and society, not least for mental health interventions and end-of-life care.